EMPOWERING PERSONS LIVING WITH DISABILITIES VIA INCLUSIVE PRACTICES IN ORGANIZED SECTORS - LEARNINGS FROM DEVELOPED NATIONS (Proceedings of the World Disability & Rehabilitation Conference, 2018)
Issue of disability has figured on International Human Rights agenda in on several occasions. The existence of disability often results in decrease in social and economic well-being. Understanding the numbers of people with disabilities and their circumstances can improve efforts to remove disabling barriers and provide services to allow people with disabilities to participate. Present research has analyzed the practices in developed nations under organized sectors to how they empower the people living with disabilities to get their rightful space in the areas of work and education. Present research has systematically reviewed research papers, reports (years 2001to 2017), case studies, epidemiological studies via online database ‘PubMed’, ‘Google Scholar’ and ‘Web of Science’. The good practices, lessons, barriers have been identified to advocate such good practices in developing nations. There is lot to learn from countries like Switzerland, Norway, Canada etc., which have the highest rates of employment for persons with disabilities. The participation of people with disabilities is important for promoting human dignity, social cohesion and accommodating the disabled working age population. There are ample of good practices in developed nations which we can adopt to make the work environment most inclusive, equitable and enabling for people living with disabilities.
Keywords: Inclusion; Disabled persons; Employment; Education